2002
DOI: 10.1080/1034912022000028358
|View full text |Cite
|
Sign up to set email alerts
|

Community Perspectives and Subjective Quality of Life

Abstract: Community integration has increasingly become the focus of research and practice in the field of intellectual disability. Recent research has demonstrated that community integration needs to be more than simply living within a community, people need to use the community and feel like they belong. This study pioneers the use of a sense of community measure to better understand the degree to which feelings of belonging are associated with quality of life. One hundred and thirty two students from both urban and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 24 publications
3
24
2
4
Order By: Relevance
“…The results showed that there was no significant difference between total Quality of Life scores of the two groups. This result is consistent with the results of Bramston, Bruggerman, and Pretty (2002), although inconsistent with other previous studies (Sands, Kozleski, & French, 2000;Watson & Keith, 2002). It was expected that the normal group would report better quality of life than the intellectually disabled group, but in this case neither group had a positive selfreport of quality of life.…”
Section: Group Comparisonssupporting
confidence: 93%
See 2 more Smart Citations
“…The results showed that there was no significant difference between total Quality of Life scores of the two groups. This result is consistent with the results of Bramston, Bruggerman, and Pretty (2002), although inconsistent with other previous studies (Sands, Kozleski, & French, 2000;Watson & Keith, 2002). It was expected that the normal group would report better quality of life than the intellectually disabled group, but in this case neither group had a positive selfreport of quality of life.…”
Section: Group Comparisonssupporting
confidence: 93%
“…This dimension addresses leisure time, leisure activities, and family gatherings. This result is inconsistent with previous studies (Bramston, et al, 2002;Watson & Keith, 2002). Social relationship activities in various environments (like leisure and family activities) often are known as the key consequences of social integrity, influencing perceptions of members of the society, belongingness, and quality of life (Mahon, et al, 2000).…”
Section: Group Comparisonscontrasting
confidence: 71%
See 1 more Smart Citation
“…Similarly, increasing awareness of the effect of community integration and inclusion for children and adolescents with intellectual disabilities has been growing. Results of an Australian study of community belongingness and LS among intellectually disabled students, for example, has indicated that LS is significantly correlated with levels of activity, friends, and support within the community (see Bramston et al 2002). Further, studies have shown that adolescents with intellectual disability report lower use of community facilities, and feel less belongingness and control over their choices than their matched peers cf.…”
Section: Mental Disabilitiesmentioning
confidence: 99%
“…Unsurprisingly, many researchers have found that emerging adults with disabilities feel as if they generally belong less than their peers (Bramston, Bruggerman, & Pretty, 2002;Hall, 2004). This lesser sense of belonging in those with a disability may be related to the increased levels of social rejection that they experience (Chen & Shu, 2012;Salmon, 2013).…”
Section: Sense Of Belonging and Need To Belongmentioning
confidence: 99%